Analisis Beban Kerja Tenaga Pendidik di SMK Kristen 1 Surakarta - Mahendra Arya Wisnu Pradana; Tutik Susilowati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to: (1) determine formulation the educator's workload; (2) knowing educator's workload at SMK Kristen 1 Surakarta. This research is mixed research with a concurrent embedded strategy, using a quantitative approach based on Permendikbud No. 15 Tahun 2018, and qualitative case studies. The population in this study is all educators. The sampling technique is quantitative with saturated sampling and qualitative with purposeful sampling. Informants include school principals, vice of curricula, and educators with non-standard workloads. Quantitative data was collected using document studies, and qualitative using interviews. Techniques for testing validity of quantitative data aren’t needed, and qualitative use triangulation credibility tests, transferability tests, dependability tests, and confirmability tests. Quantitative data analysis using simple quantitative descriptives, and qualitative using Miles and Huberman's data analysis theory. Research results: (1) the main party in formulating workload is vice of curriculum,  formulation of workload is based on Permendikud No. 15 Tahun 2018, formulation of workload is carried out at the beginning of the academic year, and already has a flow formulation; (2) results of calculating workload of educators in 2023 show that 64.52% of educators already have an inload workload, 29.03% of educators overload , and 6.45% of educators have underload workload. The problem of workload overload is caused by educators leaving school, the impact that occurs is the need to work outside of hours, the strategy used is to respond positively, time management, joint classes, student-centered learning, and collaborating with PLP students.